Psychosocial factors associated with quality of life in allogeneic stem cell transplant patients prior to transplant. Issue 6 (18th December 2013) - Pillay, Brindha; Lee, Stuart J.; Katona, Lynda; Burney, Sue; Avery, Sharon
Abstract Objectives The primary aim of this retrospective study was to determine levels of psychological distress and quality of life (QoL) immediately prior to allogeneic stem cell transplantation. The secondary aim was to examine the demographic, medical and psychosocial factors that were correlated with various QoL domains at this stage of treatment. Methods A series of measures was completed by 122 allograft patients as part of routine psychological assessment at the treating hospital prior to undergoing the transplant. These included the Mental Adjustment to Cancer Scale, the Brief Symptom Inventory‐18 and the World Health Organisation Quality of Life‐BREF. Demographic and medical data were also extracted. Results In this study, 12% and 14% of the sample experienced significant levels of depressive and anxiety symptoms, respectively. Half of the sample reported impaired physical QoL, whereas approximately 40% reported poor psychological and social QoL. Besides relationship status, the limited number of demographic (age and gender) and medical factors (disease status) tested did not contribute significantly to reported QoL. After controlling for medical and demographic factors, weaker Fighting Spirit and higher levels of depression (trend towards significance) were associated with poorer physical and social QoL. Conclusions The association among psychological distress, coping responses and QoL indicates that poor psychosocial functioning pre‐transplant renders an increased likelihood of experiencing impaired QoL across various dimensions. It thus seems important that psychologically vulnerable patients are identified early in the treatment process. If psychosocial adjustment were improved, patients may experience better QoL pre‐transplant with a potential subsequent influence on post‐transplant outcomes. Copyright © 2013 John Wiley & Sons, Ltd.